Image and Indeterminacy in Heidegger’s Schematism - Clive Cazeaux (Ergo, An Open Access Journal of Philosophy, 2021)
This paper focuses on the work to which the concept of image is put by Heidegger in his retrieval of the schematism in Kant and the Problem of Metaphysics. Whereas the schematic role of the image is never fully developed by Kant, Heidegger pays it much more attention, investing it with properties that have the potential to make the schema an active component in his own ontology. However, the motifs he uses to characterize the image depart from the conventional notion of an image as the representation of an object or scene, and are puzzling, if not to say mysterious. I show how the motifs acquire new relevance when they are considered in relation to (a) Boehm’s ‘indeterminacy’ theory of the image, and (b) the novel, ontological concept of time that Heidegger introduces. With these perspectives in mind, the motifs allow us to ‘image’ or imagine aspects of continuity that are central to Heidegger’s concept of primordial time, and therefore confirm the schema as a coherent element in his system. I also suggest how this clarified schema-image might act as a bridge between Heidegger’s philosophy before and after the turn.